41 Screening for diabetes and pre-diabetes in patients admitted with acute coronary syndrome to the university hospital limerick. (7th October 2015) - Abudlah, A; Hamra, M; Burke, D; Ahern, C; Cahill, C; Abdelrahman, M; Meany, B; Kiernan, TJ
Abstract : Introduction: Diabetes Mellitus (DM) is a major risk factor for coronary artery disease (CAD), and patients with CAD are considered high risk for the development of DM. The ESC guidelines on Diabetes, pre-diabetes and cardiovascular disease 2013 recommended screening for diabetes in patients with established cardiovascular disease. The guidelines recommended the use of both fasting blood glucose (FG) and HbA1c. Methods: We evaluated the practice of DM screening in patients admitted with acute coronary syndrome (ACS) to the University Hospital Limerick. Retrospective review of medical records of 53 consecutive patients admitted between January and February 2014 was performed. Results: 3 patients were known to have DM and excluded from analysis. The overall screening rate for DM using fasting glucose or Hb1c was 76%. (FG 76% and HbA1c in 25%). This level of practice was able to identify 5 patients (10%) with diabetic range results, and 13 patients (26%) as pre-diabetes. Intervention: A protocol was introduced to ACS care pathway and reinforced with departmental meeting. This recommended the use of both FG and HbA1c in all ACS patients. Cycle 2: We reviewed all patients admitted with ACS between November to December 2014. Out of 59, 6 were known-diabetics and excluded from analysis. Of the remaining 53, 100% of patients had screening for DM using FG (50/53) or HbA1c (45/53). The use of FG alone identified 20 patients (37.7%) as pre-diabetes, and HbA1c alone (American Diabetes Association criteria) identified 24 / 53 patients (45%) as high risk. Using both tests we were able to identify 5 patients (9.4%) with diabetic range results and 34 patients (64%) as high risk or pre-diabetes. Conclusion: Screening for DM using FG and HbA1c is recommended for patients with established CAD. This method identifies more patients with pre-diabetes for more intensive and specific rehabilitation programs.